Blockchain‐based framework for secured storage, sharing, and querying of electronic healthcare records. (20th May 2021) - Kaur, Jasleen; Rani, Rinkle; Kalra, Nidhi
Summary: Medical records contain vital, critical, and confidential information of any person. Paper‐based medical records are being used by many hospitals that suffer from various issues like large physical storage requirements, limited security, and life. Electronic health records (EHRs) can transform this entire system but faces various security threats like unintentional disclosure, tampering, data leaks, lack of security mechanisms, and data access policies. Thus, there arises a need for a decentralized, tamper‐proof, and transparent healthcare network. In this article, a permissioned blockchain‐based framework using Hyperledger Fabric (HLF) is proposed, which provides secure storage, sharing, and querying of EHRs. For better data accessibility and security, algorithms have been designed to define the functionality of patients, doctors, and third‐party administrator using smart‐contracts. In the existing approaches, LevelDB (key store database) is used as a state database that is not suitable for handling complex queries. To overcome this issue, we have used CouchDB (document store database) as a state database where the search is based on keys and data values both rather than only keys. To measure the various performance indicators for this framework, a blockchain benchmark tool "Hyperledger Caliper" is used. The experimental results show the effectiveness and efficiency of the proposed framework.